Integrated Transcriptional Profiling Analysis and Immune-Related Risk Model Construction for Intracranial Aneurysm Rupture - Shan, Dezhi; Guo, Xing; Yang, Guozheng; He, Zheng; Zhao, Rongrong; Xue, Hao; Li, Gang (Frontiers in Neuroscience, 2021)
17 Intracranial aneurysms (IAs) may cause lethal subarachnoid hemorrhage upon rupture, but the 18 molecular mechanisms are poorly understood. The aims of this study were to analyze the 19 transcriptional profiles to explore the functions and regulatory networks of differentially expressed 20 genes (DEGs) in IA rupture by bioinformatics methods and to identify the underlying mechanisms. 21 In this study, 1471 DEGs were obtained, of which 619 were upregulated and 852 were downregulated. 22 Gene enrichment analysis showed that the DEGs were mainly enriched in the inflammatory response, 23 immune response, neutrophil chemotaxis and macrophage differentiation. Related pathways include 24 the regulation of actin cytoskeleton, leukocyte transendothelial migration, nuclear factor-kappaB (NF- 25 κB) signaling pathway, Toll-like receptor signaling pathway, tumor necrosis factor (TNF) signaling 26 pathway and chemokine signaling pathway. The enrichment analysis of 20 hub genes, subnetworks 27 and significant enrichment modules of weighted gene coexpression network analysis (WGCNA) 28 showed that the inflammatory response and immune response had a causal relationship with the 29 rupture of unruptured intracranial aneurysms (UIAs). Next, the CIBERSORT method was used to 30 analyze immune cell infiltration into ruptured intracranial aneurysms (RIAs) and UIAs. Macrophage 31 infiltration into RIAs increased significantly compared with that into UIAs. The result of Principal 32 component analysis (PCA) revealed that there was difference between RIAs and UIAs in immune cell 33 infiltration. A 4-gene immune-related risk model for IA rupture (IRMIR), containing CXCR4, CXCL3, 34 CX3CL1 and CXCL16, was established using the glmnet package in R software. The receiver 35 operating characteristic (ROC) value revealed that the model represented an excellent clinical situation 36 for potential application. Enzyme-linked immunosorbent assay (ELISA) was performed and showed 37 that the concentrations of CXCR4 and CXCL3 in serum from RIA patients were significantly higher 38 than those in serum from UIA patients. Finally, a competing endogenous RNA (ceRNA) network was 39 constructed to provide a potential explanation for the mechanism of immune cell infiltration into IAs. 40 Our findings highlighted the importance of immune cell infiltration into RIAs, providing a direction 41 for further research.